PENDIDIKAN ISLAM BERWAWASAN LINGKUNGAN HIDUP PADA MADRASAH IBTIDAIYAH DI BONE SULAWESI SELATAN - Ridhwan Ridhwan; Wardhana Wardhana (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2019)
This study discusses environmentally sound Islamic education in Islamic Madrasah in Bone South Sulawesi Regency. Islamic Education summarized in Quranic Subjects Hadith, Aqidah Akhlak, Fiqih and History of Islamic Culture can be used as a medium in instilling environmentally sound Islamic education in students. This study uses a literature review approach and in-depth interviews. The findings of this study indicate that Islamic education has been integrated into the subjects of moral aqidah for example to animals and plants, while fiqh subjects such as maintaining the cleanliness of the body and the environment. Thus children learners have scientific insights which can then be practiced to love and care for the environment.